Behavioral cusp and the exclusion responding: Notes about a research program (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Behavior Analysis can contribute to the understanding of human development by benefiting from accumulated empirical research. This work explored a research program about the response by exclusion in young children considered a behavioral cusp. The notes on the program summarized a set of research that can provide empirical support to the concept. The operations that produce the exclusion responding correspond to one of the operations that simulate what is meant by listener behavior. Responding by exclusion is an early event that extends throughout life; on the other hand, listener behavior is possibly a condition to echo responding, to tact and to emit mands. The extent of the acquisition changes would require verifying empirically its impact on later changes, a challenge to be faced. Presenting an in-progress research program could suggest alternatives to the debate on a behavioral developmental analysis.
Keywords: responding by exclusion; young children; behavioral cusp; development; research program